2009
DOI: 10.1086/648086
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Influenza Vaccination Coverage among Healthcare Personnel in US Hospitals

Abstract: Hospitals vary in terms of the groups of individuals included in influenza vaccination coverage measurements. Standardized measures may improve comparability of hospital-reported vaccination rates. Measuring coverage in a manner that facilitates identification of occupational groups with low vaccination rates may inform development of targeted interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…As noted above, it also must address all the practices necessary to reduce the spread of influenza in healthcare settings, including patient isolation, use of personal protective equipment, hand hygiene, and visitor and HCP restriction when ill. Because the types of HCP included in vaccination programs may vary, with contract staff, private physicians, students, and volunteers often excluded, this recommendation applies to all HCP practicing in all healthcare settings (including contract workers, independent practitioners, volunteers, students, and product vendors), regardless of whether the HCP have direct patient contact or whether the HCP are directly employed by the facility. 57 ' 58 Exemptions to influenza vaccination mandates should be allowed only for medical contraindications to vaccination, specifically allergy to eggs and prior allergic or severe adverse reactions to influenza vaccine. Such exemptions should be adequately documented and reviewed before allowing exemption from this requirement.…”
Section: R E V I S E D Shea P O S I T I O N On I N F L U E N Zmentioning
confidence: 99%
“…As noted above, it also must address all the practices necessary to reduce the spread of influenza in healthcare settings, including patient isolation, use of personal protective equipment, hand hygiene, and visitor and HCP restriction when ill. Because the types of HCP included in vaccination programs may vary, with contract staff, private physicians, students, and volunteers often excluded, this recommendation applies to all HCP practicing in all healthcare settings (including contract workers, independent practitioners, volunteers, students, and product vendors), regardless of whether the HCP have direct patient contact or whether the HCP are directly employed by the facility. 57 ' 58 Exemptions to influenza vaccination mandates should be allowed only for medical contraindications to vaccination, specifically allergy to eggs and prior allergic or severe adverse reactions to influenza vaccine. Such exemptions should be adequately documented and reviewed before allowing exemption from this requirement.…”
Section: R E V I S E D Shea P O S I T I O N On I N F L U E N Zmentioning
confidence: 99%
“…Following a CDC survey of U.S. hospitals in 2006, the American Medical Association estimated an HCW influenza vaccination rate of 55% in participating facilities and 46% nationally (Lindley, Yonek, Ahmed, Perz, & Torres, 2009). Using 2004–2008 National Health Interview Survey data, Caban‐Martinez et al (2010) conclude that less than half of workers in health care occupations had received an influenza vaccination between 2004 and 2008, with annual rates ranging from 36.8% to 49.0%.…”
Section: Introductionmentioning
confidence: 99%
“…A study from 2006 found that most hospitals measured influenza vaccination coverage for employees, but fewer hospitals measured coverage for nonemployee HCP or included coverage of vaccine refusal or contraindication. 2 …”
Section: Discussionmentioning
confidence: 99%